Evaluating Systemic Toxicity in Rabbits after Acute Ocular Exposure to Irritant Chemicals. (19th November 2014) - Cherian, Reshma Sebastian; Parayanthala Valappil, Mohanan
Abstract : Acute systemic toxicity via ocular exposure route is not a well understood aspect. Any material/drug/chemical that comes in contact with the eye can evade the first pass metabolism and enter the systemic circulation through the conjunctival blood vessels or via the nasolacrimal route. In this study, the effect of ocular irritant chemicals on the systemic toxicity was assessed in rabbit. Eyes of rabbits were exposed to known ocular irritant (cetyl pyridinium chloride, sodium salicylate, imidazole, acetaminophen, and nicotinamide) for 24 h and scored. After a period of 72 h, blood was collected from the animals for examining the hematological and biochemical parameters. The animals were then sacrificed and the eyes were collected for histopathology and cytokine analysis by ELISA. Splenocyte proliferation was assessed by tritiated thymidine incorporation assay. The liver and brain of the treated animals were retrieved for evaluating oxidative damage. The chemicals showed moderate to severe eye irritation. Inflammation was not evident in the histopathology but proinflammatory markers were significantly high. The splenocyte proliferation capacity was undeterred. And there was minimal oxidative stress in the brain and liver. In conclusion, acute exposure of ocular irritants was incapable of producing a prominent systemic side effect in the current scenario.